The Gentle Light: John Henry Newman - Leenman, Dirk (Razón y fe, 2019)
This article traces the spiritual journey of Blessed John Henry Cardinal Newman from his conversion as a teenager in 1816 to his reception in the Catholic Church in 1845, through his journey through the Mediterranean in 1832-1833. It also addresses his position within the Oxford Movement, the failure of his Middle Way Theory and his attempt to give a Catholic interpretation to Anglicanism. Considering the conversion of 1845 as the fruit of the spiritual experience of 1816, I hold that in this whole process there is not only rupture, but also continuity.
Keywords: conversion; Catholicism; Anglicanism; Oxford Movement